ATRT-24. CHROMATIN SEGMENTATION IN ATRT REVEALS AN IMPORTANT ROLE FOR RESIDUAL SWI/SNF MEMBERS - Johann, Pascal (Neuro Oncol, 2018)
Although SMARCB1 mutations represent the only recurrent genetic aberration in atypical teratoid/rhabdoid tumors (ATRT), a comprehensive assessment of the epigenetic effect of SMARCB1 loss has not been attempted so far. To achieve this, we performed ChIP-sequencing for six histone marks (H3K4me1, H3K4me3, H3K27me3, H3K27Ac, H3K9me3, H3K36me3) and EZH2 in 11 primary ATRTs, encompassing all three molecular subgroups of ATRT. Chromatin segmentation analyses revealed that across all three subgroups a high percentage of ATRT epigenomes resides in a quiescent state and active enhancer states are significantly underrepresented as compared to non-neoplastic brain. We validated these findings in a SMARCB1-reexpressing ATRT cell line and also found an overall deincrease of H3K27Ac and H3K27me3 upon SMARCB1 reexpression. Interestingly, by comparing the genome wide distribution of EZH2 and H3K27me3, we also identified classes of ATRT-specific active genes bound by EZH2, but lackingH3K27me3, pointing at a non-canonical role of EZH2 in gene activation. ChIP-Sequencing of SMARCA4 in these samples revealed that many of these „EZH2 only” genes display a high signal of of this protein. Many of these genes (such as e.g. CCND2) were downregulated upon knock-down of SMARCA4 in ATRT cell lines. Adding to the overall characterization of the epigenome, we have shown that a number of genes - despite being bound by EZH2- are maintained in an active state by residual SWI/SNF complex binding. This sheds new light on the role of residual SWI/SNFSMARCA4 still being present in AT/RT and elucidates a mechanism by which AT/RT keep important tumor-genes in an active state.